Teaching Writing in English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Teaching writing in English can be a difficult task, specifically with the diverse range of skills and abilities that students can contribute to the classroom. Nevertheless, there is a possibility to help students improve their writing skills and become more confident in expressing themselves in English, if right approach and techniques are used. This article will discuss a variety of techniques and methods for teaching writing in English, including how to create a supportive and engaging learning environment, providing feedbacks feedback, and incorporating a wide range of writing tasks and exercises. We will also explore the role of grammar and vocabulary instruction in the writing processess using of technology to improve students’ writing skills.